804. Impact of Azithromycin Prophylaxis in Lung Transplant Recipients on the Risk of Nontuberculous Mycobacterial Infections. (26th November 2018) - Workman, Adrienne; Kaza, Vaidehi; Bennett, Scott; Chong, Pearlie
Abstract: Background: Azithromycin has been shown to improve FEV1 in lung transplant recipients (LTR) with bronchiolitis obliterans syndrome (BOS). The impact of azithromycin use on the incidence of infections due to Mycobacterium avium complex (MAC) and M. abscessus in LTR is currently unknown. Methods: We conducted a nested case–control study of a retrospective cohort of adult LTR transplanted between 2007 and 2017. Cases were defined as LTR with nontuberculous mycobacterial (NTM) infections due to MAC and/or M. abscessus. Controls were defined as LTR without NTM infections. NTM infection was defined by presence of pulmonary symptoms and radiographic changes (clinical criteria) in addition to positive cultures from ≥2 sputa or ≥1 bronchial specimens (microbiological criteria) according to the IDSA/ATS criteria. LTR who meet microbiological, but not clinical criteria were considered colonized and not included for analysis. Azithromycin use was defined as ≥90 days for BOS treatment. Results: Among 538 LTR, 60% (321/538) were male and 81% (434/538) received double LTs. Indication for LT was idiopathic pulmonary fibrosis (28% [152/538]), chronic obstructive pulmonary disease (23% [121/538]), cystic fibrosis [CF] (13% [68/538]), and other (37% [197/538]). The overall incidence of NTM infections was 4.3% (23/538); of which 65.2% (15/23), 17.4% (4/23), and 17.4% (4/23) were due to MAC, M. abscessus and polymicrobial infections, respectively. Thirty-one percent (165/538) of LTR received azithromycin. LTR who received azithromycin prophylaxis had 0.21 times the odds of developing NTM infections compared with LTR who did not receive azithromycin prophylaxis (OR: 0.21, 95% CI: 0.02 – 0.86, P = 0.02). Age ( P = 0.88), type of LT ( P = 0.81), pretransplant NTM colonization ( P = 0.46), and CF ( P = 0.22) were evaluated as possible risk factors, but were not associated with increased risk of developing NTM infections in bivariable analyses. In a multivariable logistic regression model, azithromycin prophylaxis was independently associated with decreased risk of NTM infections after adjusting for CF and pretransplant NTM colonization (aOR: 0.20, 95% CI: 0.05–0.88, P = 0.01). Conclusion: Azithromycin use was associated with lower risk of NTM infections due to M. abscessus and MAC in our LTR. Disclosures: All authors: No reported disclosures.